A high-performance self-powered broadband photodetector based on a CH3NH3PbI3 perovskite/ZnO nanorod array heterostructure. Issue 30 (15th July 2016) - Yu, Jichao; Chen, Xu; Wang, Yi; Zhou, Hai; Xue, Mengni; Xu, Yang; Li, Zhaosong; Ye, Cong; Zhang, Jun; van Aken, Peter A.; Lund, Peter D.; Wang, Hao
Abstract : An FTO/ZnO-nanorod/CH3 NH3 PbI3 /MoO3 /Au photodetector exhibited high performance and can achieve self-powered, broadband light detection, high detectivity and responsivity, robust and high stability. Abstract : Here we report a self-powered photodetector based on a ZnO/CH3 NH3 PbI3 heterojunction and a MoO3 hole-transport layer. The organolead iodide perovskite photodetector is sensitive to broadband wavelengths from the ultraviolet light to the entire visible light region (250–800 nm), showing a high photo-responsivity of 24.3 A W −1 and a high detectivity value of 3.56 × 10 14 cm Hz 1/2 W −1 at 500 nm without external bias voltage. Meanwhile, we found that the photodetective performances are closely related to the thickness of the MoO3 layer, which acts as a hole-transport layer and an electron-blocking layer and can effectively decrease the recombination of holes and electrons. Additionally, the as-fabricated photodetector exhibits good stability and only 9.3% photoelectric response current decay after a 3-month illumination test. The high detectivity and responsivity of such a ZnO nanorod/perovskite heterojunction are clearly demonstrated and should be widely applicable to other photoelectric detection devices.